2018
DOI: 10.1029/2017gb005852
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Maintenance of the GEOTRACES Subsurface‐Dissolved Iron Maxima in an Ocean Biogeochemistry Model

Abstract: Recent GEOTRACES transects revealed basin‐scale patterns of dissolved iron in the global oceans, providing a unique opportunity to test numerical models and to improve our understanding of the iron cycling. Subsurface maxima of dissolved iron in the upper ocean thermocline are observed in various transects, which can play an important role in regulating marine productivity due to their proximity to the surface euphotic layer. An ocean biogeochemistry model with refined parameterizations of iron cycling is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 90 publications
4
39
0
Order By: Relevance
“…Accordingly, a more detailed model including a weaker ligand and larger concentration of total ligand has led to better model-measurement agreement (Parekh et al 2004). Currently, some ocean biogeochemistry models consider variability in Fe-binding ligands (Misumi et al 2013;Völker & Tagliabue, 2015;Pham & Ito, 2018), although some still assume a constant ligand concentration of 0.6 or 1 nM (Tagliabue et al 2016). Furthermore, few ocean biogeochemistry models consider scavenging of Fe onto mineral dust, in addition to the scavenging on organic particles (Moore & Braucher, 2008;Aumont et al 2015;Ye & Völker, 2017;Pham & Ito, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a more detailed model including a weaker ligand and larger concentration of total ligand has led to better model-measurement agreement (Parekh et al 2004). Currently, some ocean biogeochemistry models consider variability in Fe-binding ligands (Misumi et al 2013;Völker & Tagliabue, 2015;Pham & Ito, 2018), although some still assume a constant ligand concentration of 0.6 or 1 nM (Tagliabue et al 2016). Furthermore, few ocean biogeochemistry models consider scavenging of Fe onto mineral dust, in addition to the scavenging on organic particles (Moore & Braucher, 2008;Aumont et al 2015;Ye & Völker, 2017;Pham & Ito, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Biological production is modulated by the availability of nutrients (PO 3− 4 and dFe) and light through Monod function. As in Pham and Ito (2018), we consider three external supplies for dFe: atmospheric deposition, continental shelves, and hydrothermal vents. In this model, the biological Fe:P uptake ratio changes as a function of the dFe concentration, which aims to represent the luxury Fe uptake of diatoms such as in the subarctic Pacific and the Southern Ocean (Ingall et al, 2013).…”
Section: Model Configurationmentioning
confidence: 99%
“…There is uncertainty in the binding strength of the refractory, humic-like L 3 , as several studies reported to be weaker than 10 11 L/mol (Gledhill & Buck, 2012); thus, we vary the magnitude of K L3 between 10 11 and 10 10 L/mol in the sensitivity experiments. The two-class parameterization of Pham and Ito (2018) is essentially the same as setting K L3 = K L2 = 10 11 L/mol, so a decreased retention of dFe is anticipated if we use K L3 < 10 11 L/mol. dFe not bound to ligands (free Fe, [Fe ′ ]) can be removed from the water column by scavenging onto lithogenic and organic particles, based on a first-order bulk scavenging rate, and by precipitation (Pham & Ito, 2018).…”
Section: Model Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fe tracer in the model is the sum of the two forms dF e = F eL + F e . F e is calculated as in Parekh et al (2004) and represents only a small percentage of the total dFe pool. It is assumed that Fe and ligands are bound in a 1:1 ratio.…”
Section: Organic Complexationmentioning
confidence: 99%